Comparative Analysis of Random Blood Glucose Levels Based on Waist Circumference Among Personnel at Pakupatan Terminal - Hilda Zakiyya Zamzamy; Widia Pangestika; Astri Ayu Novaria; Rifatul Masrikhiyah (Universitas Teuku Umar, 2026)
Central obesity, measured by waist circumference, is a key anthropometric indicator and a major risk factor for Type 2 Diabetes Mellitus (T2DM). The prevalence of central obesity and metabolic disorders continues to increase globally and locally, including in Serang City. Certain occupational groups, such as terminal personnel, may be at higher risk due to sedentary work patterns and occupational stress. This study aimed to examine differences in Random Blood Glucose (RBG) levels based on central obesity status among personnel at Pakupatan Terminal, Serang City. A cross-sectional design was employed, involving 23 management and operational personnel selected through convenience sampling in November 2025. Data were collected through waist circumference measurements and RBG testing, and analyzed using descriptive statistics and the Independent Samples t-test. The results showed a p-value greater than 0.05, indicating no significant difference in RBG levels between central obesity and normal groups. This finding may be influenced by the small sample size or early metabolic changes not yet reflected in glucose levels. Despite the non-significant results, central obesity remains an important indicator of long-term metabolic risk. Therefore, preventive interventions such as workplace health screening, nutrition education, and regular physical activity are recommended to reduce the risk of metabolic syndrome and other non-communicable diseases among high-risk occupational groups.